Religion and the Pathologization of Fandom: Religion, Reason, and Controversy in My Little Pony Fandom. - Crome, Andrew (Journal of Religion & Popular Culture)
Popular media and academic studies have often compared media fandom to a form of secularized religion, suggesting excessive and irrational involvement. Fans respond to this charge by emphasizing rational elements of their fandom and the imagined worlds they explore. This article examines fan response when the rationality of this imagined world is undermined through the fan object itself, focusing on Brony (adult My Little Pony) fandom: a fandom often perceived by fans as pathologized in the media. Fans have highlighted their role as cultural gate-keepers, protecting children from irrationality and recasting the text into an attack on poor scientific method, or have used fandom as a forum to discuss religion. This article argues that the "fandom as religion" metaphor patologizes both religion and fandom and ignores the diversity of fan responses to religion.